2018
DOI: 10.1038/s41398-018-0092-z
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala hyper-connectivity in a mouse model of unpredictable early life stress

Abstract: Childhood maltreatment is associated with a wide range of psychopathologies including anxiety that emerge in childhood and in many cases persist in adulthood. Increased amygdala activation in response to threat and abnormal amygdala connectivity with frontolimbic brain regions, such as the hippocampus and the prefrontal cortex, are some of the most consistent findings seen in individuals exposed to childhood maltreatment. The underlying mechanisms responsible for these changes are difficult to study in humans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
99
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 76 publications
17
99
0
3
Order By: Relevance
“…Previous studies have shown that humans exposed to ELS have increased connectivity at amygdala in association with individual hyperreactivity (Johnson, Delpech et al 2018). This is in concordance with our results showing that normal pruning of granule cells AISS by microglia is impaired by maternal separation.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that humans exposed to ELS have increased connectivity at amygdala in association with individual hyperreactivity (Johnson, Delpech et al 2018). This is in concordance with our results showing that normal pruning of granule cells AISS by microglia is impaired by maternal separation.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple lines of research have implicated both the BLA and the dmPFC (plPFC in rodents) as critical nodal structures involved in the pathophysiology of stress-related affective disorders (Carlisi and Robinson, 2018;Kalisch and Gerlicher, 2014;Milad et al, 2009;Ongur and Price, 2000;Preuss, 1995;Robinson et al, 2014). The rodent plPFC has extensive reciprocal glutamatergic connections with the BLA that are modulated by stress exposure and capable of generating anxiety-like responses (Felix-Ortiz et al, 2015;Johnson et al, 2018;Lowery-Gionta et al, 2018;Vertes, 2004). In order to investigate the molecular mechanisms regulating BLA-plPFC connectivity and plasticity, we first sought to verify that this circuit is engaged by exposure to stressful stimuli (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple lines of research have implicated both the BLA and the dmPFC (plPFC in rodents) as critical nodal structures involved in the pathophysiology of stress-related affective disorders (Carlisi and Robinson, 2018;Kalisch and Gerlicher, 2014;Milad et al, 2009;Ongur and Price, 2000;Preuss, 1995;Robinson et al, 2014). The rodent plPFC has extensive reciprocal glutamatergic connections with the BLA that are modulated by stress exposure and capable of generating anxiety-like responses (Felix-Ortiz et al, 2015;Johnson et al, 2018;Lowery-Gionta et al, 2018;Vertes, 2004). In order to investigate the molecular mechanisms regulating BLA-plPFC connectivity and plasticity, we first sought to verify that this circuit is engaged by exposure to stressful stimuli (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%